Characterisation of skin spectra in a Caucasian and Oriental sample - Xiao, Kaida; Wang, Mengmeng; Luo, Ronnier; Li, Changjun; Wuerger, Sophie (Electronic Imaging, 2016)
Accurate spectral measurements of facial skin are important for numerous medical applications including the diagnosis and treatment of cutaneous disorders and the provision of maxillofacial soft tissue prostheses. In this study we obtained calibrated facial and body skin spectra (forehead, cheek, neck) from two ethnic groups (Caucasian and Oriental) with a view of establishing a new skin spectral database for medical and cosmetic applications. Skin spectra for 188 subjects were measured using a Tele-spectroradiometer (PR650) in a large viewing booth with controlled lighting. The grand mean of skin spectra for Caucasians and Oriental females were calculated and their spectral difference between different ethnic groups and body areas were assessed. Our main findings are: (1) The shape of the skin spectra reflectance functions is similar for both ethnic groups, but differs across body locations. (2) Spectral variation (expressed as RMSE) between different body areas is significantly larger in the Oriental compared to the Caucasian sample (by a factor of ∼2). (3) Largest ethnic differences occur in the neck area, and the smallest in the cheek.